An Observation of Transferring Management Knowledge for Seaweed Cultivation Community in Semporna, Sabah - Roslinah Mahmud; Roselina Ahmad Saufi; Durrishah Idrus; Harcharanjit Singh a/l Mahinder; Junainah Jaidi (2020)
Knowledge Transfer Programme (KTP) is introduced by the Ministry of Education (MOE) Malaysia to link the collaborations between the Malaysian local universities, industries and communities to continue to flourish. This paper aims to observe the achievement of the seaweed cultivation management system in Semporna, Sabah under KTP project. The project involves the transfer of knowledge related to the management from the university to the staff of industry partners and local seaweed farmers. This project introduces the knowledge in seaweed cultivation in a modern, systematic, and proper manner to the seaweed farming management. The knowledge transfer included farming and office, human capital, and financial management. After two years, the project objectives have been achieved. The seaweed farms have been better managed and organized, production and sales were increased, and staff management skills have been successfully developed.